2005
DOI: 10.1542/peds.2004-1981
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Factors That Affect Successful Diabetes Management for Their Children

Abstract: Clinicians can affect many of the factors that parents perceive to make a difference in whether they can successfully raise a resilient child in good diabetes control. Future research needs to determine whether health care teams that address the concerns that parents raised in this study are more effective in guiding children to cope well with diabetes, to incorporate healthier lifestyles, and ultimately to achieve better metabolic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 39 publications
1
59
0
2
Order By: Relevance
“…Parents, too, expect education to be a central part of every office visit (Ginsburg et al, 2005). From their interactions with providers, parents want expert medical advice to create a diabetes treatment plan that is integrated into their child's and family's life; parents also want support around basic parenting skills as they raise a child with diabetes (Howe, Ayala, Dumser, Buzby, & Murphy, 2012).…”
Section: Goalsmentioning
confidence: 99%
“…Parents, too, expect education to be a central part of every office visit (Ginsburg et al, 2005). From their interactions with providers, parents want expert medical advice to create a diabetes treatment plan that is integrated into their child's and family's life; parents also want support around basic parenting skills as they raise a child with diabetes (Howe, Ayala, Dumser, Buzby, & Murphy, 2012).…”
Section: Goalsmentioning
confidence: 99%
“…Racial disparities exist in the treatment and outcomes of children with type 1 diabetes. It has been shown that black children with type 1 diabetes have poorer metabolic control (21)(22)(23)(24). A ninefold increased risk of death was demonstrated for young African Americans with diabetes in Chicago, compared with non-Hispanic white patients with type 1 diabetes over an 8-year period (25).…”
Section: Conclusion -In 1990mentioning
confidence: 99%
“…We are currently expanding our research to identify goals and priorities of our patients/ families with diabetes with the purpose of informing clinicians of some of the differences between white and black families to get a better sense of how to most effectively serve these families (24).…”
Section: Conclusion -In 1990mentioning
confidence: 99%
“…27,28 Although age plays an important role in how influential these factors are, their relevance remains altogether consistent from early childhood to adulthood and thus is worth a second look.…”
mentioning
confidence: 99%